Chemical risk assessment in hospital settings: A comparison of workers' perceptions, expert opinions, and occupational hygiene measurements - Ayşe Coşkun Beyan; Gamze Tuna; Esra Emerce; Gül İşlekel (Nofer Institute of Occupational Medicine, 2023)
Background Harmful chemicals are used in various forms from different sources in hospital settings. The standard gold method in risk control studies still determines exposure by personal or ambient measurements. In the absence of trained personnel, resources, or sufficient time, qualitative methods should be used to assess exposure. This study aims to compare quantitative and qualitative results of chemical risk exposure. Material and Methods Both qualitative (perceptions without monitoring data of the workers and experts) and quantitative perceptions (perceptions with monitoring data) were recorded. Two experts were asked to evaluate exposure intensity in pathology department workers, secretary workers, and cleaning workers. Occupational hygiene measurements were taken based on the occupational health and safety department risk assessment results, expert job analysis, and pilot study measurements. Results While most workers reported feeling highly exposed to chemical risks, the majority of experts reported medium-risk exposures and high-risk exposures. Three occupational hygiene measurements (6.6%) exceeded the permissible time-weighted average, and the other results were within the acceptable range. Conclusions There was a significant difference between the estimated exposure and the measured exposure in hospital settings. A correlation was not found between workers' perceptions of chemical risk exposure and the chemical risk levels measured in this study. Med Pr Work Health Saf. 2023;74(4):241-50.